Eksplorasi Penggambaran pada Material Bergambar sebagai Lukis Alternatif - Rahim, Muhamad Ali; Suryana, Wawan; Septiadi, Abdusyukur Budiarvin (Ideas Publishing, 2024)
The discourse on shifting artistic idioms which allows for the opening up of diversity in the visual creation of paintings is the background for this applied research. The aim is to offer alternative materials for paintings that add novelty to the idea of creation. The method used is based on practice and experimentation through the use of used pictorial media as a field for painting. This research produces alternative works of painting with visual uniqueness due to the overlapping images as a differentiator. Apart from marking a paradigm shift in the discourse and idiom of painting, it also strengthens the findings regarding the transfer of the basic material context of painting. This creation is quite important because the exploration of unconventional painting presents uniqueness that can trigger newness in painting in the future.